Challenges involved in measuring intake in early life: focus on methods. Issue 2 (20th February 2014) - Foster, Emma; Adamson, Ashley
Abstract : Assessing dietary intake in people of any age is challenging but measuring the diet of infants and children can be particularly problematic. Young children may lack the cognitive skills, writing skills and food knowledge to record their own food intake. Multiple people may be responsible for the care of the child and to collect an accurate picture of intake it may be necessary to combine parental reports with observation in school or nursery. Where interviews are conducted with the child themselves questions may need to focus on aspects of the diet which children are likely to attend to. For example, children may not be familiar with food names or brands but may be able to describe their texture, colour and images on packaging. Adolescents are likely to be more aware of the foods they consume and have the cognitive and writing skills to record their own food intake but may lack the interest or motivation. Research has focused on reducing the burden of recording intake on the participant. Developments include food photographs for assessment of portion size which remove the need for weighing each food item, and, in recent years, computer-based methods have been developed for self-completion by young people with the aim of motivating them to participate in studies by making dietary reporting more engaging. The present paper discusses methods and challenges in assessing food intake in children followed by details of two such tools developed at Newcastle University, UK, the Young Person's Food Atlas and INTAKE24.